Simulation of losses in a three-phase bank of transformers in the presence of harmonic distortion - Grau-Merconchin, Frank; Hernández Areu, Orestes; Nuñez Alvarez, José Ricardo; Montenegro-Romero, Michael; Quintero-Ospino, Oscar (Institute of Advanced Engineering and Science, 2024)
The load losses of the transformers increase considerably with the presence of harmonic distortion in the currents. Its increase can be determined using an analytical method based on ANSI/IEEE Standard C57.110. On the other hand, when it comes to three-phase banks with transformers of different capacities, delta connections, or incomplete connections, the analytical method does not allow the losses to be accurately estimated, which is why digital simulation is necessary. This work presents an adjusted model to determine the load losses in a three-phase bank of three single-phase transformers with different connection schemes. The model allows for determining load and electrical losses and calculating total additional losses. It is also possible to decide on the load capacity of the bank's transformers, the power factor, and the efficiency with which they operate under these conditions.